The role of changes in metabolic syndrome status on health-related quality of life in Bogor City, West Java, Indonesia: A cross-sectional study - Indriyati, Titi; Adisasmita, Asri C.; Nadjib, Mardiati; Subekti, Imam; Hatma, Ratna Djuwita; Kosen, Soewarta; Riyadina, Woro; Purnamasari, Telly (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Metabolic syndrome (MetS) is a cluster of chronic conditions, including central obesity, hypertension, impaired glucose metabolism, and dyslipidemia (low HDL, high LDL, and triglycerides). A diagnosis of MetS is made when three or more of these symptoms are present. If left unmanaged, MetS can lead to serious health complications such as cardiovascular disease and type 2 diabetes. Over time, individuals with MetS may experience a decline in their health-related quality of life (HRQoL), especially due to its chronic nature. Objective: This study aimed to evaluate the effects of changes in MetS status on HRQoL. Methods: This study employed a cross-sectional design. Secondary data from the cohort study of Non-Communicable Disease (NCD) risk factors, conducted by the Health Research and Development Agency of the Ministry of Health of the Republic of Indonesia in Bogor City, was used. Data from four follow-up periods (2011/2012 to 2017/2018) were analyzed. A total of 874 respondents were selected via total sampling based on inclusion and exclusion criteria. Data were collected in 2021, which included measures of knowledge, health check-ups, and HRQoL using the SF-36 questionnaire. Statistical analyses, including chi-square tests, t-tests, and multiple regression analyses, were conducted to examine the associations between MetS status and HRQoL. Results: Descriptive analysis revealed that 19% (171 participants) had worsened MetS status, while 80.4% (703 participants) showed improvement. Chi-Square analysis found that respondents with worsening MetS status were 1.6 times more likely to experience poor HRQoL in the physical dimension (95% CI = 1.1-2.3), but no significant effect was found for the mental dimension (PR = 1.1, 95% CI = 0.8-1.6). Multiple logistic regression analysis revealed that comorbidities interacted with worsening MetS status to significantly affect HRQoL in the physical dimension. The adjusted prevalence ratios (PR) were 27.5 (95% CI = 10.3-73.2) for those with comorbidities and 9.2 (95% CI = 5.7-15.0) for those without comorbidities, after controlling for age, mental health, BMI changes, routine health checks, and knowledge. Conclusion: Changes in MetS status towards worsening have a significant negative effect on HRQoL, particularly in the physical dimension. The presence of comorbidities in individuals with worsening MetS status greatly increases the risk of poor HRQoL. Healthcare professionals and nurses should consider the interaction between MetS and comorbidities in patient management. Nurses are encouraged to monitor HRQoL in patients with MetS, promote education on managing comorbidities, and collaborate across disciplines to enhance patient care and intervention programs aimed at improving HRQoL.